Efficacy and safety of dupilumab in two adolescents with severe atopic dermatitis - Giavina-Bianchi,Mara (2021)
ABSTRACT We report the cases of two adolescent siblings with severe atopic dermatitis, who, despite weighing approximately 40kg, presented a good response to dupilumab with the off-label dose for individuals aged 12 years and weighing 60kg. Both had already used cyclosporine, azathioprine, methotrexate and oral corticosteroids for long periods, plus topical treatments with no adequate disease control. Skin lesions were constant and widespread, with frequent skin infections and very poor quality of life, with numerous physical and psychosocial consequences, such as dropping out of school activities due to severe itching, appearance and bullying. They also showed delayed growth and development. In 2018, dupilumab, an immunobiological agent, was approved for treatment of moderate to severe atopic dermatitis in adults and, in 2019, extended to the 12-17-year age group. Although it had already been approved by the Brazilian Health Surveillance Agency, the 200mg presentation (indicated for the weight of patients) was not available, with no expected arrival date. Therefore, weighing the risks and benefits of the situation of both, we chose to treat them with an adult dose (loading dose of 600mg subcutaneously, and 300mg subcutaneously every 2 weeks) despite the low weight. So far, they have received eight injections, showing significant improvement of disease and quality of life. There were no major adverse effects, only worsening of allergic conjunctivitis in one of them. The patients and their family are very satisfied, and we believe that the therapy has been successful.